A Case Study of Nearshore Wave Transformation Processes along the Coast of Mexico near the Laguna Verde Nuclear Power Plant Using a Fast Simulation Method. (3rd January 2011) - Herrera-Díaz, Israel-Enrique; Couder-Castañeda, Carlos; Ramírez-León, Hermilo
Abstract : A numerical model based on the mild-slope equation of water wave propagation over complicated bathymetry, taking into account the combined effects of refraction, diffraction, and reflection due to breakwater, is presented. The numerical method was developed using a split proposed version of the mild-slope equation and solved by an implicit method in a finite volume grid; this technique easily allows model the wave effects caused by the breakwater building in coastal waters, where industrial and other economic activities take place. Controlled case studies have been made and the results match very well with the reference solution. The capability and utility of the model for real coastal areas are illustrated by application to the breakwater of the Laguna Verde Nuclear Power Plant (LVNPP).